Agama Dan Sains Modern: Agama, Sains - Muhammad Sutan Maulana (Jurnal Penelitian Multidisiplin, 2022)
Religion is based on wayu which is in the form of the holy book al-Qur'an. For scientists, the Qur'an is a source of knowledge that is safe for all kinds of scientific disciplines to be developed. Sharia sciences such as Aqidah, fiqh, kalam, philosophy without denying disciplines such as astronomy, medicine, physics, chemistry. Modern science denies the role of religion in scientific studies. So that in the end, modern science distanced itself from religious doctrine. In this case, it examines the status (position) of religion in the perspective of Islamic science and modern science with studies that emphasize textual aspects. It was concluded that religion is inherently inseparable from science. Islamic science adheres to the deen or religion, while modern science is no longer based on religion, thus accumulating the damage it causes. This triggers Muslim scientists to take a response, namely by offering a solution to the idea of Islamization of modern science. Just as religion also has its own method for uncovering meaning, but the two should not mutually negate each other's existence. Even though science and religion have their respective areas of jurisdiction, they can share one another.